An interface damage model that captures crack propagation at the microscale in cortical bone using XFEM. (February 2019) - Gustafsson, Anna; Khayyeri, Hanifeh; Wallin, Mathias; Isaksson, Hanna
Abstract: Reliable tools for fracture risk assessment are necessary to handle the challenge with an aging population and the increasing occurrence of bone fractures. As it is currently difficult to measure local damage parameters experimentally, computational models could be used to provide insight into how cortical bone microstructure and material properties contribute to the fracture resistance. In this study, a model for crack propagation in 2D at the microscale in cortical bone was developed using the extended finite element method (XFEM). By combining the maximum principal strain criterion with an additional interface damage formulation in the cement line, the model could capture crack deflections at the osteon boundaries as observed in experiments. The model was used to analyze how the Haversian canal and the interface strength of the cement line affected the crack trajectory in models depicting osteons with three different orientations in 2D. Weak cement line interfaces were found to reorient the propagating cracks while models with strong interfaces predicted crack trajectories that penetrated the cement line and propagated through the osteons. The presented model is a promising tool that could be used to analyze how local, age-related material changes influence the crack trajectory and fracture resistance in cortical bone. Graphical abstract: Highlights: The XFEM model can simulate crack propagation in cortical bone at the microscale. The model is applicable to osteons with three perpendicular orientations. The interface damage model can capture crack deflections at osteon boundaries. The strength of the cement line interface has great influence on the crack path.